The Use of Cohesive Devices in Theses Abstracts Written by Undergraduate Students of English Department - Muhammad Akif Alwi; Fani Indrawan (Bilingua, 2023)
This study aims to find out the types of cohesive devices used by undergraduate students of English department in their theses’ abstracts and to find out the most and least dominant types of cohesive devices in their theses’ abstracts. The writer used corpus-based study as his research design. The data is taken from fifty randomly selected undergraduate theses’ abstracts written by English department students of IAIN Kediri. The technique of collecting data is documentation. This study exposes two main findings. First, the type of cohesive devices that are employed in undergraduate students’ theses’ abstracts, which are shown by reference (2051 items), conjunction (593 items), substitution (56 items), ellipsis (30 items), repetition (141 items), synonymy (40 items), antonymy (13 items). Second, the mostly used cohesive devices type by undergraduate students in their theses’ abstracts are reference with 2051 items (70.34%) occurrences and the least is antonymy with 13 items (0.44%) occurrences.